Adiponectin stimulates glucose uptake in mouse blastocysts and embryonic carcinoma cells. Issue 3 (March 2020) - Burkuš, J; Navarrete Santos, A; Schindler, M; Babeľová, J; Jung, J S; Špirková, A; Kšiňanová, M; Kovaříková, V; Fischer, B; Koppel, J; Fabian, D; Čikoš, Š
Abstract : Preimplantation embryos are sensitive to maternal hormones affecting embryonic signal transduction and metabolic functions. We examined whether adiponectin, the most abundantly secreted adipokine, can influence glucose transport in mouse embryonic cells. In mouse blastocysts full-length adiponectin stimulated glucose uptake, while no effect of globular adiponectin was found. Full-length adiponectin stimulated translocation of GLUT8 glucose transporter to the cell membrane; we did not detect significant changes in the intracellular localization of GLUT4 glucose transporter in adiponectin-treated blastocysts. To study adiponectin signaling in detail, we used embryoid bodies formed from mouse embryonic carcinoma cell (ECC) line P19. We confirmed the expression of adiponectin receptors in these cells. Similar to mouse blastocysts, full-length adiponectin, but not globular adiponectin, stimulated glucose uptake in ECC P19 embryoid bodies. Moreover, full-length adiponectin stimulated AMPK and p38 MAPK phosphorylation. These results indicate that besides AMPK, p38 MAPK is a potential target of adiponectin in mouse embryonic cells. AMPK inhibitor did not influence the adiponectin-stimulated p38 MAPK phosphorylation, indicating independent action of these two signaling pathways. In mouse embryos adiponectin acts as a hormonal regulator of glucose uptake, which becomes especially important in phases with reduced levels of circulating insulin. Our results suggest that adiponectin maintains the glucose supply for early embryos under hypoinsulinaemic conditions, for example, in mothers suffering from type 1 diabetes mellitus.